First in situ observations of soft bottom megafauna from the Cascais Canyon head - Gomes-Pereira, José N. (2016)
We report the first in situ observations of soft bottom megafauna from the Cascais Canyon head. Observations were collected opportunistically during three technical dives with the ROV Luso between 460-805 m at two locations distanced 1,230 m. The habitats were clas-sified as upper bathyal fine mud. The soft bottom fauna was dominated by burrows of Nephrops norvegicus reaching up to 2.9 burrows/m2, a common habitat along the Portu-guese continental margin. To our knowledge, densities are the highest ever reported for depths below 300 m. The ichthyofauna at the upper Cascais Canyon is a mixture of lower shelf and upper bathyal species, including Phycis blennoides, Scyliorhynus canicula, Coe-lorhynchus labiatus/occa and Chimaera monstrosa. Bait release attracted Myxine glutinosa. Surveys in other geological settings of the Cascays Canyon are required to understand more comprehensively the diversity of its sessile and vagile biodiversity.